THE REALIZATION OF THE CONCEPT OF “BLOOD-RELATIVE” IN ENGLISH AND UZBEK - Mavludakhon, Ulikova (Confrencea, 2024)
According to Webster's third new International dictionary of the English Language, Königemann, 1993, a “blood-related” concept in the noun phrase category, the term began to come into contact in 18331. Focusing on its meanings in the dictionary: kinship 2 - the quality or state of being kin. Kinship3 - affinity, connection, relation, association, relationship, bearing, linkage liaison.